Wajh al-Dalalah al-Qur’aniyah fi Kalimati Al-Sahab - Mujib Abdurrahman; Jannita Nanda Solichatin (Studia Quranika, 2020)
The word of As-Sahab is the types of object in which is assumed as a sign of rain because most of the context which explained As-Sahab in Al-Qur’an is followed by rain. However, in the other verses, As-Sahab is interpreted as a cloud that cover the sunlight without followed by rain. After examine the word “Cloud” in Al Quran, there are several possibilities. Several cloud has water content. In addition, “cloud” has diverse nature which has explained in Al Qur’an with diffferent word. Therefore, what is the meaning of As-Sahab in arabic term? What is the characteristic of word As-Sahab as a Cloud in the other explanation? This study aimed to describe the meaning of As-Sahab and several words that have similar meaning so that it will find the exactly word. It also will be known each features in Interpretation of Al-Qur’an. It is revealed that As-Sahab is Sahabah in plural form. The other meaning is Ghaym. However. The word ‘Cloud” in Al-Qur’an has many features such Cloud which float in the sky,The heavy cloud, the piled up cloud. Allah has distinguished cloud base on its movement. While, Ghamam is interpreted as a cloud which cover sunlight. This cloud is assumed without followed by rain. Rakham is the type of Piled up cloud followed by rain. Muzni means collect. It means that there are water content in cloud. The last, Mu’sirat is the feature of cloud which produce rain after collected.